MIMO-OFDM Channel Estimation Using ANFIS - Seyman, M. N.; Taspinar, N. (Elektronika ir Elektrotechnika, 2012)
In this paper, adaptive neuro fuzzy inference system (ANFIS) model is proposed for channel estimation in MIMO-OFDM system and the performance of this estimator is compared to the least square error (LS), least mean square error (LMS) algorithms by computer simulations. According to the simulations, ANFIS performs better than LS and LMS algorithms. Moreover, there is no need of sending pilot tones which are necessary for classical algorithms, in ANFIS. Therefore the ANFIS is bandwidth efficient algorithm. Ill. 4, bibl. 15, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.120.4.1458